2021
DOI: 10.3390/su13084147
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Experiential Value of Augmented Reality: The Context of Heritage Tourism

Abstract: The use of information boards tends to be regulated in many heritage sites to preserve these cultural heritage places. Although augmented reality (AR) has become a major approach for reducing negative experiences due to restrictions, limited studies have been conducted to understand the effect of AR experiential value on destination-related behavior. Accordingly, the current work aims to investigate how the multidimensional components of AR experiential value (i.e., visual appeal, entertainment, enjoyment, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 74 publications
(122 reference statements)
0
14
0
1
Order By: Relevance
“…Rahman, Sabbir, Surajit and et al (2021) aimed to investigate tourist willingness to conduct a medical tourism revisiting and suggested that stakeholders should focus on the hedonic/emotional and utilitarian/functional, and economic factors of the destination [40]. Some researchers, such as Seokho, Yoon, Ji-Hwan, and Jookyung (2021), investigated how the multidimensional components of AR experiential value (i.e., visual appeal, entertainment, enjoyment, and escapism) affect supportive behavior through AR satisfaction [41].…”
Section: Experience Value Satisfaction and Revisit Intentionsmentioning
confidence: 99%
“…Rahman, Sabbir, Surajit and et al (2021) aimed to investigate tourist willingness to conduct a medical tourism revisiting and suggested that stakeholders should focus on the hedonic/emotional and utilitarian/functional, and economic factors of the destination [40]. Some researchers, such as Seokho, Yoon, Ji-Hwan, and Jookyung (2021), investigated how the multidimensional components of AR experiential value (i.e., visual appeal, entertainment, enjoyment, and escapism) affect supportive behavior through AR satisfaction [41].…”
Section: Experience Value Satisfaction and Revisit Intentionsmentioning
confidence: 99%
“…Verma et al (1999) found that diners from certain cultures desire more visual stimulation in their menus than others to foster a desire to purchase a menu item. Visual appeal has been shown to exert a positive effect on experiential authenticity (Han, Yoon, & Kwon, 2021); however, the relationships among menus' visual appeal and customers' perceived authenticity have not been extensively delineated in the existing literature.…”
Section: Menus' Visual Appealmentioning
confidence: 99%
“…The offer of an immersive experience determines and influences user satisfaction [2,66]. This is confirmed also in the tourism sector [67]. Authors found that VR can have a positive impact on customer satisfaction and loyalty [68] and that VT satisfaction enhances positive consumer behavioral intentions [69].…”
Section: Hypothesis 5 (H5) Enjoyment Exerts a Positive Effect On Vr T...mentioning
confidence: 80%
“…Specifically, we measured the intention to visit the Parmigiano Reggiano production site using a three-item scale derived by De Canio et al [21], Papagiannidis et al [72], and Fiore et al [38]. We used a four-item scale derived by Jung et al [73] and Han et al [67] to measure VR tour satisfaction (4 items). We measured enjoyment using a four-item scale derived from the recent study of De Canio et al [1], while the four items used to measure the ease-of-use construct, as well as the four items used to measure the presence construct, are derived from Georgiou et al [74].…”
Section: Methodsmentioning
confidence: 99%